Penerapan metodologi ilmiah dalam kegiatan akademik mahasiswa - Diana, Diana; As’ari, Erham (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
The application of scientific methodology in academic activities is indirectly aimed at developing critical, systematic, and objective thinking skills among university students. Scientific methodology serves not only as a set of technical procedures in research but also as an implicit scientific mode of thinking that underpins academic practices in higher education, including the preparation of scholarly writing, course assignments, and student research activities. This article seeks to conceptually examine the application of scientific methodology in students’ academic activities. It outlines the foundational understanding, stages of implementation, and common challenges encountered in academic practice. This study adopts a qualitative approach based on a literature review by examining various relevant sources from previous studies, including academic textbooks and scholarly journal articles. The findings indicate that the application of scientific methodology in students’ academic activities remains constrained by several challenges, such as limited methodological understanding, a weak culture of scientific literacy, and the lack of sustained integration of scientific approaches in the learning process. Therefore, strengthening research methodology instruction and fostering continuous scientific practice are essential to improving the quality of academic activities in higher education.